Confirmation practice in pharmacogenetic testing: how good is good enough? - Lunenburg, Carin; Neumaier, Michael (Clinica chimica acta, 2019)
Pharmacogenetic testing is increasingly implemented in routine diagnostics. However, quality control measures, in particular confirmation practices e.g. the use of two independent genotyping techniques, are subject of debate and there are no clear guidelines. The aim of the current paper is to discuss the current practice in confirmation testing in the field of pharmacogenetics and draw attention to this situation. DPYD genotyping is used as a case example to highlight the importance of assigning the correct genotype. Current confirmation practices in laboratories are explored through a survey. Substantial heterogeneity was observed with 54% of the laboratories applying different forms of confirmation practice. Finally, we evaluated over 10years of genotyping results from two large genotyping facilities, which both use a second, independent genotyping technique. Discrepancies between tests were identified in 9 patients (0.01%), possibly due to allele dropout. We feel that a second, independent technique is useful for genetic tests with a high clinical impact, such as DPYD testing. Guidelines can help to align confirmatory laboratory practices for pharmacogenetics, which may need to be specified per gene and test.